“LogiHire”- The bridge between Truckers and Employers - Sunnatkhonova, Shakhodatkhon (2025)
There are significant challenges present within the U.S. logistics staffing sector, primarily due to increasing driver shortages, high median driver age, high turnover rates, as well as inefficient hiring processes. This thesis aims to create a comprehensive business plan for a company – LogiHire, a digital staffing platform dedicated to solving the constraints observed within the trucking industry. Within the theoretical segment of the thesis, the strategic and analytical frameworks are covered, including Business Model Canvas, PESTLE analysis, SWOT analysis, Porters Five Forces and Marketing Mix. Within the practical segment of the thesis, these frameworks are applied in order to construct a data-driven and scalable business plan. The resulting business plan outlines how LogiHire aims to alleviate the pain points of the trucking industry by increasing the efficiency of the hiring process, expanding the talent pool, as well as improving the quality of matches between carriers and drivers to reduce the turnover rate. Financial projections and risk mitigation strategies are adopted in order to further support the feasibility and scalability of the adopted business model. Overall, this thesis provides a strategic plan for LogiHire to address barriers within the logistics staffing sector, demonstrating how an innovative digitalized approach can contribute to the industry by improving the recruiting processes as well as retention.